Role of ADMA in the pathogenesis of microvascular complications in type 2 diabetes mellitus - Guo, Xinyang; Xing, Yiqiao; Jin, Wei (Frontiers in Endocrinology, 2023)
Diabetic microangiopathy is a typical and severe problem in diabetics, including diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, and diabetic cardiomyopathy. Patients with type 2 diabetes and diabetic microvascular complications have significantly elevated levels of Asymmetric dimethylarginine (ADMA), which is an endogenous inhibitor of nitric oxide synthase (NOS). ADMA facilitates the occurrence and progression of microvascular complications in type 2 diabetes through its effects on endothelial cell function, oxidative stress damage, inflammation, and fibrosis. This paper reviews the association between ADMA and microvascular complications of diabetes and elucidates the underlying mechanisms by which ADMA contributes to these complications. It provides a new idea and method for the prevention and treatment of microvascular complications in type 2 diabetes.